Characterization of Bismuth Composited to Carbon Nanotube-Coated Titanium Cathode in Electro-Fenton System - Yi-Ta Wang; Yi-Chi Hsieh; Yue-Sheng Lin (Nanomaterials and Nanotechnology)
Bismuth (Bi) is a highly reactive catalyst for the generation of hydroxyl (∙OH) radicals. Cathodes constructed from composites of Bi and carbon nanotube (CNT) exhibit high stability and low resistance, which enhance their electron transfer capability. In this work, a titanium substrate was coated with multi-walled carbon nanotube (MWCNT/Ti) using electrophoretic deposition process, followed by electrodeposition of Bi onto the MWCNT-coated Ti (Bi/MWCNT/Ti). The effects of Bi electrodeposition time on the surface morphology of Bi/MWCNT/Ti cathodes were investigated by scanning electron microscopy and energy-dispersive X-ray spectroscopy, and the electrochemical characteristics of each cathode were identified via a series of electrochemical analyses further. The results demonstrated that electrodeposition at −0.85 V vs. Ag/AgCl for 5 min revealed uniform distribution of dense Bi across the surface of cathode, which provides better hydrophilicity for cathode and promotes highest electron transfer rates, respectively; when the Bi/MWCNT/Ti cathode was used as an electro-Fenton (EF) cathode, the EF system achieved a rhodamine B degradation rate of 80.8% after 30 min, which is a significant increase (83.63%) than the unmodified Ti cathode. The use of Bi in EF cathodes improves the efficiency of the EF process.